Artificial intelligence technologies in social insurance - Zahorska , D.; Danylkina, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2023)
The article discusses the possibilities of using artificial intelligence in the field of social insurance. The relevance of the topic and the importance of using artificial intelligence technology in this area are established, since it can improve the activities of the insurance sector and solve various problems. The purpose of the work is to study the specifics of the use of artificial intelligence technologies in social insurance and their impact. The paper examines current technologies and areas of artificial intelligence application. The software solutions used by social insurance authorities are thoroughly disclosed. It is determined that artificial intelligence technologies are used in social insurance for data analysis, risk forecasting and decision-making. The functions and capabilities of artificial intelligence in this area are widely disclosed in the article. It is established that these technologies can be used to process large amounts of information, to collect customer data, to predict risks, or as a virtual for risk forecasting or as virtual assistants. The author analyzes the challenges and risks that arise when using technology. It is determined that the main ones are problems with confidentiality and access to technology. Options and methods for solving problems are proposed, such as data regulation, development of ethical standards, increasing transparency, etc. In addition, the advantages of using technology in the field of social insurance are identified. These include increased work efficiency, improved quality of service, and reduced fraud. Conclusions are drawn that show that the use of artificial intelligence technologies in the field of social insurance has great potential. This contributes to the development of insurance companies and improvement of their work.